2013
DOI: 10.1371/journal.pone.0062473
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA from Leishmania (Viannia): Accuracy of Polymerase Chain Reaction for the Diagnosis of Cutaneous Leishmaniasis

Abstract: Cutaneous leishmaniasis (CL) can occur in skin and mucosa, causing disfiguring lesions. The laboratory diagnosis of CL involves immunological methods and optical detection of the parasite, al of which have limitations. There is a need for more effective diagnostic methods for CL which wil allow treatment to be initiated more promptly in order to help prevent the development of severe forms of mucosal disease, and to estimate the prognosis of the infection. The polymerase chain reaction (PCR) has been widely us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…The samples were amplified and subsequently subjected to agarose gel electrophoresis according to the protocol provided by Nietzke-Abreu et al (2013). The reaction mixture (25 µL) contained 1 µM of each primer (Invitrogen), 1.5 mM MgCl 2 , 1X enzyme buffer, 0.2 mM dNTP (Invitrogen), 1 U Taq DNA polymerase (Invitrogen) and 2 µL of the sample DNA.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…The samples were amplified and subsequently subjected to agarose gel electrophoresis according to the protocol provided by Nietzke-Abreu et al (2013). The reaction mixture (25 µL) contained 1 µM of each primer (Invitrogen), 1.5 mM MgCl 2 , 1X enzyme buffer, 0.2 mM dNTP (Invitrogen), 1 U Taq DNA polymerase (Invitrogen) and 2 µL of the sample DNA.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…Vergel and others 11 detected the presence of Leishmania DNA in 7.5% of skin lesions and in 19.2% in peripheral-blood monocytes isolated from 59 patients with confirmed diagnosis of CL. In a recent study, Neitzke-Abreu and others 21 reported the identification of Leishmania DNA in 83.87% of skin lesions and 51.67% of peripheral-blood monocytes isolated from 106 patients with CL. The percentages of Leishmania DNA detected in the studies described above are lower than the percentage of Leishmania DNA detected in the skin and whole blood of the present study.…”
mentioning
confidence: 96%
“…11,12,21 Venazzi and others, 12 studying 68 patients with CL, detected parasite DNA in 3.4% of prepared blood samples. In that study, blood samples were treated with a solution containing 25 mM citric acid, 50 mM sodium citrate, and 81 mM glucose before DNA isolation.…”
mentioning
confidence: 99%
“…The mucosal form of CL, which manifests as destructive and mutilating injuries in the mucous membranes of the upper airways, is estimated to occur in 3-5% of cases (2) . In State of Paraná, the mucosal form was identifi ed in 23.1% of cases in 2010, indicating a higher prevalence of this form of the disease compared to other Brazil States (4) .…”
mentioning
confidence: 99%
“…All samples were tested for the presence of possible inhibitors of PCR by using specifi c primers for the human β-globin gene (GH20: 5'-GAA GAG CCA AGG ACA GGT AC-3' and PC04: 5'-CAA CTT CAT CCA CGT TCA CC-3') (9) , intended to amplify a fragment of 268bp (4) .…”
mentioning
confidence: 99%